2020
DOI: 10.1002/cncr.32946
|View full text |Cite
|
Sign up to set email alerts
|

Why individual‐level interventions are not enough: Systems‐level determinants of oral anticancer medication adherence

Abstract: Nonadherence to oral anticancer medications (OAMs) in the United States is as low as 33% for some cancers. The reasons for nonadherence to these lifesaving medications are multifactorial, yet the majority of studies focus on patient‐level factors influencing uptake and adherence. Individually based interventions to increase patient adherence have not been effective, and this warrants attention to factors at the payor, pharmaceutical, and clinical systems levels. Based on the authors' research and clinical expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(23 citation statements)
references
References 56 publications
(120 reference statements)
0
23
0
Order By: Relevance
“…In prior work, we found that parity laws had relatively small effects on out-of-pocket spending overall, but may have benefited some patients with very high out-of-pocket spending on OAMs. 14,15 However, parity is a benefit for individuals enrolled in fully-insured plans and excludes approximately half of the commercially insured (those in self-funded plans-presumably the "loophole" mentioned by Dean et al) 2 , as well as the largest group of anticancer medication users-Medicare Part D beneficiaries. Although federal proposals would expand parity to self-funded plans and to states that have not yet passed these laws, additional efforts would be needed to ensure that Medicare beneficiaries (particularly those covered by Part D) have sufficient out-of-pocket protections for their anticancer treatments.…”
Section: Increasing Generic Drug Utilizationmentioning
confidence: 99%
See 4 more Smart Citations
“…In prior work, we found that parity laws had relatively small effects on out-of-pocket spending overall, but may have benefited some patients with very high out-of-pocket spending on OAMs. 14,15 However, parity is a benefit for individuals enrolled in fully-insured plans and excludes approximately half of the commercially insured (those in self-funded plans-presumably the "loophole" mentioned by Dean et al) 2 , as well as the largest group of anticancer medication users-Medicare Part D beneficiaries. Although federal proposals would expand parity to self-funded plans and to states that have not yet passed these laws, additional efforts would be needed to ensure that Medicare beneficiaries (particularly those covered by Part D) have sufficient out-of-pocket protections for their anticancer treatments.…”
Section: Increasing Generic Drug Utilizationmentioning
confidence: 99%
“…Dean et al 2 recommend multiple cost‐reduction strategies that target state and federal policies and various actors across the pharmaceutical supply chain. Specifically, the authors call for increasing generic utilization, “closing the loopholes” in oral chemotherapy parity laws, sharing rebates with patients at the point of sale, and addressing the appropriateness of high‐cost medications when lower cost treatments are available.…”
Section: Overview Of Proposed Payer and Pharmaceutical System Intervementioning
confidence: 99%
See 3 more Smart Citations